The role of Lewis acidic vanadium centers in DME steam reforming over V-Ni catalysts - González-Gil, Rafael; Kovalik, P.; Antoniak-Jurak, K.; Lewalska-Graczyk, A.; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; Pieta, P.; Nowakowski, R.; Pieta, I.S.; Alemany-Arrebola, Luis José (Elsevier, 2012)
Dimethyl ether (DME) as a potential chemical storage of renewable energy was studied for decomposition and steam reforming (DME SR) to produce hydrogen-rich streams over V-Ni/Al2O3 catalysts. The extent of DME decomposition, DME hydrolysis, and subsequent methanol steam reforming was examined during this study, focusing on the redox and acid/base properties of catalyst surface species. The results show that the DME SR performance depended on the acid-redox character of the Ni-O-Ni/V-O-Ni species dispersed onto alumina. For S/ C ratio close to 2.5, for relative V-rich catalysts, DME hydrolysis reaction over the Lewis acid sites was found a rate-determining step and then, metallic centers being responsible for H2 and CO2 production. For 3V-Ni/Al2O3 DME SR with low selectivity towards methane and direct H2 and CO2 production (H2/CO2 ratios close to 3), with near-complete DME conversion was obtained above 673 K.
Keywords: Catálisis; Procesos químicos; DME steam reforming; Hydrogen storage; Methanol reforming; V-Ni catalysts; in situ FTIR studies